ISOLATION AND CHARACTERIZATION OF FUNGAL LIPASE STRAINFROM OIL SPILLED SOILS - Lakkakula Bhagya Lakshmi, M.Raghu Ram (International Journal of Modern Agriculture, 2021)
A total of 17pure fungal lipolytic strains were isolated from five vegetable oil contaminated soil samples collected from five oil mills located in different areas of Guntur district, Andhra Pradesh, India. The fungal isolates were screened for the production of lipase enzyme, qualitatively using Tributyrin Agar medium and Olive oil -Rhodamine-B agar media. Out of the 17 isolated, two strains (rm-104 and rm-125) showed high lipase activity with large hydrolysis zones, were identified based on their morphological characteristics as Penicillium sp. These two strains produced 0.155±0.007 IUmL-1 and 0.105±0.002 IUmL-1 of enzyme at pH 6 and 37°C ± 2°Crespectively in the basal medium. The strain with high enzyme production, rm 104, was identified as Penicillium citrinum basing on the 18s rRNA sequencing data, and the sequence was deposited in gene bank with accession number KU613360.Thus, this straincan be considered as good source for extracellular lipase production under slightly acidic conditions.